Zirconium based metal-organic framework in-situ assisted hydrothermal pretreatment and enzymatic hydrolysis of Platanus X acerifolia exfoliating bark for bioethanol production. (May 2019) - Ahmed, Ibrahim Nasser; Yang, Xiu-Li; Dubale, Amare Aregahegn; Shao, Rong; Guan, Rong-Feng; Meng, Xiangming; Xie, Ming-Hua
Highlights: New strategies of UiO-66 assisted hydrothermal pretreatment and saccharification. UiO-66 MOF catalyze hydrolysis of glycoside bonds of dimer sugar. UiO-66 assisted pretreatment is far better than simple hydrothermal method. The enzymatic hydrolysis together with UiO-66 cocatalysis afforded higher TRS. Abstract: Metal-organic framework (MOF) assisted hydrothermal pretreatment and co-catalysis strategy based on UiO-66 MOF is developed for the first time. The Planetree exfoliating bark was pretreated with or without UiO-66 assisted hydrothermal method at a temperature ranging from 160 to 240 °C for 1–3 h residence. With the rise of pretreatment severity, the total reducing sugar (TRS) was increased till reached maximum, 180 mg g −1, in the presence of UiO-66. The fitting models validate the optimal hydrothermal condition was at 180 °C and 1 h, which was characterized with high TRS and very low yield of furfural and HMF. The TRS from enzymatic hydrolysis reaches maximum, 391 mg g −1, in the presence of MOF co-catalysis and the maximum ethanol yield achieved was 73%. Altered morphology, higher surface area and porosity are noticed after MOF assisted hydrothermal pretreatment. This study insights the MOFs' application in lignocellulose biomass processing.